2022
DOI: 10.1155/2022/8024979
|View full text |Cite
|
Sign up to set email alerts
|

Selection of lncRNAs That Influence the Prognosis of Osteosarcoma Based on Copy Number Variation Data

Abstract: Osteosarcoma is the most common primary malignancy in the musculoskeletal system. It is reported that copy number variation- (CNV-) derived lncRNAs contribute to the progression of osteosarcoma. However, whether CNV-derived lncRNAs affect the prognosis of osteosarcoma remains unclear. Here, we obtained osteosarcoma-related CNV data and gene expression profiles from The Cancer Genome Atlas (TCGA) database. CNV landscape analysis indicated that copy number amplification of lncRNAs was more frequent than deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
4
4
0
Order By: Relevance
“…Moreover, the GSEA analysis of signaling pathways revealed signi cant enrichment of RAMP1 in the olfactory transduction processes, providing insight into the mechanisms underlying its prognostic role. Consistent with the current conclusion, earlier research has indicated that olfactory transduction processes may be a potential mechanism associated with OS prognosis 24 . In addition, the KEGG pathway analysis revealed an abundance of genes involved in the Hippo and Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the GSEA analysis of signaling pathways revealed signi cant enrichment of RAMP1 in the olfactory transduction processes, providing insight into the mechanisms underlying its prognostic role. Consistent with the current conclusion, earlier research has indicated that olfactory transduction processes may be a potential mechanism associated with OS prognosis 24 . In addition, the KEGG pathway analysis revealed an abundance of genes involved in the Hippo and Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the GSEA analysis of signaling pathways revealed significant enrichment of RAMP1 in the olfactory transduction processes, providing insight into the mechanisms underlying its prognostic role. Consistent with the current conclusion, earlier research has indicated that olfactory transduction processes may be a potential mechanism associated with OS prognosis [ 25 ]. In addition, the KEGG pathway analysis revealed an abundance of genes involved in the Hippo and Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The study of Zhang et al [ 25 ] and Yang et al [ 26 ] were included into our study to compare the AUC values between our model and their models. By comparing the AUC values of 1-year, 3-years, and 5-years between models, we found that the model in our study was more effective (Figures 6(j–l) ).…”
Section: Resultsmentioning
confidence: 99%